Glyceriformia Fauchald, 1977 (Annelida: “Polychaeta”) from Lizard Island, Great Barrier Reef, Australia - Böggemann, Markus (Zootaxa, 2015)
Eight species of Glyceridae (Glycera brevicirris, Glycera cf. lapidum, Glycera onomichiensis, Glycera sagittariae, Glycera tesselata, Glycera tridactyla, Glycerella magellanica, Hemipodia cf. simplex) and six species of Goniadidae (Goniada antipoda, Goniada cf. brunnea, Goniada echinulata, Goniada emerita, Goniada grahami, Goniada paucidens) have been collected during several expeditions to the vicinity of Lizard Island (Australia, Queensland). An identification key to the Glyceriformia that inhabit the region is presented. Detailed and illustrated morphological descriptions are given for all investigated species.